New ways of predicting violent incidents in clinical settings - Turner, Katie (2014)
Aggressive behaviour in people with intellectual disability is a far reaching problem, estimated to be expressed by 7% of the population of people with intellectual disability. People with intellectual disability who are aggressive often experience an inequality in service provision. Carers who work in aggressive environments can find the management of aggression an overwhelming challenge and may suffer burnout. At a service level, providing suitable care for people who may be aggressive, whilst also providing a comprehensive care package, is very difficult. Aggression in people with intellectual disability is more prevalent than in equivalent cared for groups, but there is little research to date on the sequential nature of that aggression. Like all behaviour, aggression occurs as part of a sequence, and a crucial part of understanding violent behaviour in people with intellectual disability is to understand the nature of their aggression, and especially the (temporal) structure of these episodes, as well as the potential factors involved. Current research in aggression in people with intellectual disability focuses on the nature of static risk factors, mental health issues and the function that aggressive behaviour provides for the individual expressing it. The main aim of this thesis is to document the patterns of aggressive behaviour in people with intellectual disability in order to examine what factors may be involved in increasing the risk of aggression in this population. Guidance as to what those factors may be was taken from research into aggression in the general and intellectual disability population. The first phase of this study involved creating a database of violent incidents from the health care records of 18 participants, drawn from three National Health Service units for Intellectual Disability. These were collated into an aggressive incident database that brought together information from different sources about individual incidents. The patterns in the incidents were used to construct a typology of aggression. The second phase of the study formed the main focus of the research, and involved analysing the aggressive incident database using Sequence Analysis methods. The pattern of these results indicated that reports focused mainly on aggression that involved staff, and found visits, outings and denial of requests by participants were significant factors in the sequence of an aggressive incident. The third phase focused on data drawn from a risk management system called Sentinel, and examined all aggressive incidents occurring across three units for people with intellectual disability over four and a half years to investigate temporal patterns of aggression using time interval analysis. This was used to identify distinct temporal patterns of aggression for each of the three units involved in the study. The results indicated that visits and outings, meal times and requests were part of the sequence of aggression behaviour in people with intellectual disability. The possible implications of this were discussed, and these findings related to the wider literature.